Variation in chick-a-dee call sequences, not in the fine structure of chick-a-dee calls, influences mobbing behaviour in mixed-species flocks. (27th September 2019) - Landsborough, Blaine; Wilson, David R; Mennill, Daniel J
Abstract: When animals vocalize under the threat of predation, variation in the structure of calls can play a vital role in survival. The chick-a-dee calls of chickadees and titmice provide a model system for studying communication in such contexts. In previous studies, birds' responses to chick-a-dee calls covaried with call structure, but also with unmeasured and correlated parameters of the calling sequence, including duty cycle (the proportion of the calling sequence when a signal was present). In this study, we exposed flocks of Black-capped Chickadees ( Poecile atricapillus ) and heterospecific birds to playback of chick-a-dee calls and taxidermic models of predators. We quantified birds' responses to variation in number of D notes and duty cycle of the signalling sequence. Chickadees and heterospecific birds responded more intensely to high-duty-cycle treatments, and equally to treatments where duty cycle was held constant and the number of D notes varied. Although our study does not disentangle the effects of call rate and duty cycle, it is the first to investigate independently the behavioural responses of birds to variation in structural and sequence-level parameters of the chick-a-dee call during a predator confrontation. Critically, our results confirm that the pattern previously observed in a feeding context holds true in a mobbing context: variation in calling sequences, not in call structure, is the salient acoustic feature of chick-a-dee calls. These results call into question the idea that chick-a-dee call structure carries allometric information about predator size, suggesting instead that sequence-level parameters play a central role in communication in a mobbing context. Lay Summary: Many animals use vocalizations when mobbing predators. Vocal behavior may communicate information about the threat posed by the predator. Using playback of chick-a-dee calls during a simulated predator confrontation, we show that birds respond more intensely to treatments with greater vocal output, but do not respond differently to calls that differ in the number of dee notes. Our results reveal that variation in calling sequences plays a central role in communication in a mobbing context.